PENGARUH KEBIJAKAN UTANG, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PROPERTI DAN REAL ESTATE - Mega Wulandari, - (2019)
This study aims to determine the effect of Debt Policy proxied by Debt to Equity Ratio (der), Investment Decision proxied by Price Earning Ratio (PER) and Profitability proxied by Return On Equity (ROE) toward Firm Value proxied by Price Book Value (PBV). Population in this study are companies of property, real estate and building constaction sector listed in Indonesia Stock Exchange (IDX) 2015-2017. The technique of determination of the sample using the method of purposive sampling and obtained 31 property and real estate sub-sector companies with a research period of three years to obtain 93 units of samples. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.5 program and significance level of 5%. The result of the research shows that (1) Debt Policy (DER) has a positive effect on Firm Value (PBV), (2) Investment Decision (PER) has a positive effect on Firm Value (PBV), (3) Profitability (ROE) has no effect on firm value (PBV).